Perceived stress, coping strategies and psychological well-being of people with diabetes and people without diabetes in Bangladesh : a comparative study - Aktar, Rumana; Satu, Farhana Yeasmin (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of the present study was to investigate whether there is any difference between individuals with diabetes and without diabetes in their perceived stress, use of coping strategies and psychological well-being. A comparative study was conducted on 240 Bangladeshi adult participants. Among them 120 participants were with diabetes ranging in age from 27 through 56 years (M = 40.10 years, SD = 6.86) and 120 were healthy persons without diabetes and their mean age was 41.07 years (SD = 6.81), with a range from 31 to 59 years. They were equally distributed according to sex. No significant differences were found between the two groups in their age, occupation, educational level, monthly family income using χ2 and Mann-Whitney U test. Data were collected using a package of self-report measures including: (1) the Bangla version of perceived stress scale (2) the Bangla version of coping scale (3) the Bangla version of psychological well-being scale and (4) Personal information form. The Results of Mann Whitney U test showed significant differences between participants with diabetes and participants without diabetes in perceived stress, coping strategies and psychological well-being. The findings suggest implications for healthcare practitioners to pay attention to psychological state of patients with diabetes. This research suggests that more research should explore the psychological state of poorly versus well controlled patients with diabetes.